Konsep Taman Edukasi pada Sekolah Dasar di Kota Malang (Studi Kasus: SDN Lowokwaru 3 Malang) - Setyabudi, Irawan; Nuraini, Nuraini; Alfian, Rizki; Nailufar, Balqis (Departemen Arsitektur Fakultas Teknik Universitas Brawijaya, Indonesia, 2017)
The yard is an open space that has potential to be developed as a garden area and pavement, but many people think garden is only a waste land that utilization and modest from the surrounding buildings. The study focused on the school yard with the main building serving as education. Generally students learn in the classroom until after receiving lessons, it sometimes leads to psychological pressure to students such as stress that impact on learning outcomes. One of the architectural healing functions is the provision of a functionally and aesthetically designed garden. The research started with Focus Group Discussion (FGD) with school committee of SD Lowokwaru 3 Malang which discussed the need of garden design. The garden is divided into certain zones such as esthetic, productive, and vertical garden zone with simple technology. The garden is not only a passive garden or consumed visually, but students can also be involved directly about the process of making, maintaining and managing it. The purpose of this research is to provide alternative model of recreational and educational garden design for students, while the specific target is to study problems in school garden, analyze, and produce educational garden concept. The research method is conducted qualitatively with architectural design which ends on the concept and follow Gold and Rustam Hakim’s thinking, with adjustment to agricultural science and education. The result of the research is the division of zoning of garden space based on educational space and playing in the concept of architectural design along with the selection of vegetation. The conclusion of this research is the garden as outdoor education facility for school students.Keywords: garden, concept, recreative-educative, and outdoor learning